EVALUATING FINANCIAL PERFORMANCES OF TURKISH MANUFACTURING COMPANIES BEFORE AND AFTER REDENOMINATION - Gunadi, Venisca .; Lambey, Linda .; Tasik, Hizkia H.D (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Redenomination is simplification of nominal value of currency without reducing the real value of the money. Over 30 countries in the world had redenominated their currency. Previous researches had been discussed the reason behind redenomination, the adaptation process, the impact from economy perspective and also from business perspective. This paper aims to discuss much further about the impact of redenomination from business perspective with real case and evidence, more than just a prediction and opinion. Turkish manufacturing companies are selected to be the sample of research to mirror what may occur in Indonesian manufacturing companies. Financial statement analysis is used to describe the performance of the companies before and after redenomination. Wilcoxon Test, Mann Whitney U Test, and Multiple Linear Regression are used to analyze the data. This paper finds that redenomination does not have significant effect on the companies financial performance. The findings also suggest that profitability of firms decreases at the year of redenomination. Additionally, there is a significant increase in sales after redenomination due to the presence of money illusion. This research recommends that at the year of redenomination companies should be focusing on themselves instead of making strategies to face redenomination. Companies must be ready with the supply to make sure all demand will be fulfilled. Companies must also manage its operating cost, so the higher demand and sales will not result in an excessive operating cost. Keywords: redenomination, turkish companies, financial performance